Mapping the Conditions of Scientific Literacy and Social Literacy of Elementary School Students: Qualitative Analysis - Anistia Rizki Khoirun Nisa; Herpratiwi; Dwi Yulianti; Sumarti; Muhammad Nurwahidin; Hasan Hariri; Sunyono Sunyono; Rabiyatul Adawiyah Siregar (ISEJ : Indonesian Science Education Journal, 2025)
Scientific literacy and social literacy are essential competencies that should be developed from the early stages of formal education, particularly within integrated science and social studies learning. This study aims to map the current condition of elementary school students’ scientific and social literacy in Integrated Science and Social Studies learning in Lampung Province, Indonesia. A qualitative approach with a descriptive exploratory design was employed to obtain an in-depth understanding of students’ literacy conditions in authentic classroom contexts. The research participants consisted of elementary school teachers and students selected through purposive sampling based on their direct involvement in Integrated Science and Social Studies instruction. Data were collected through classroom observations, semi-structured interviews, and documentation studies involving lesson modules, textbooks, and student worksheets. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing/verification. Data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that students’ scientific literacy remains at a basic level. Students were generally able to observe phenomena but experienced difficulty in reasoning, interpreting information, explaining causal relationships, and applying concepts to real-life contexts. Similarly, students’ social literacy had developed in terms of basic interaction and group work but had not yet reached the level of critical social understanding and reflective social reasoning. These conditions were influenced by the dominance of conventional teaching methods, limited exploratory activities, weak contextualization of learning materials, and suboptimal use of technology. This study implies that strengthening students’ scientific and social literacy requires a transformation of instructional practices toward more inquiry-based, contextual, reflective, and student-centered learning.